The relationship between competitive experience and performance in skeleton - Mosey, T. J.; McGuigan, M. R. (Journal of Athletic Enhancement, 2014)
Introduction: The purpose of this study was to determine if a relationship exists between competitive experience and performance in skeleton. Methods: We obtained official rankings, chronological age, years of competitive experience and years in the national team from 2007- 2013 of internationally competitive World Cup competitors, from the international federations website. Chronological age, competitive experience and international competitive experience at World Cup level were correlated with end of season World Cup ranking. A total of 138 competitors (78 men and 60 women) qualified for inclusion in the study based upon World Cup ranking over the seasons analysed. Effect size (ES) was also used to compare between men and women. Results: Results showed that men were moderately older (28.9- 30.8 vs. 26.5-29.2 years, ES=0.66) and had moderately higher competitive ages (7.7-9.6 vs. 5.7-8.1, ES=0.66) than women across seasons. Moderate correlations were found between performance and competitive age (-0.59) in two seasons for men. Discussion: We showed small to moderate correlations between performance and chronological age in men and women competitors in skeleton. We also showed men were older than women in all seasons of analysis and that men had an older competitive age than women. The results indicated that men had moderate correlations between competitive experience and performance compared to women. Conclusion: Talent transfer of younger women competitors before younger men into skeleton may result in higher rankings or results in a shorter timeframe.